Optimalisasi Pemanfaatan Kolam Retensi sebagai Elemen Lanskap Berkelanjutan pada Kawasan Pendidikan Perkotaan - Rachmayanie, Arieska Avianda; Sari, Suzanna Ratih; Rizani, M. Debby (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 8 No 2 (2021): Oktober 2021, 2021)
A retention pond is one of the flood control structures, which most is made for functional purposes, with no considerations for alternative objectives. Diponegoro University has a retention pond on its campus. However, it has not been used optimally. Its capacity to contain water has shrunk due to silting, and its surrounding environment has been long neglected. In its goal to enhance the use of this retention fond as an outdoor element, this study calculates and analyses the pertinent existing conditions of this retention pond. It aims to determine its potential as a long-term flood controller and to optimize its use as part of a sustainable landscape element in an urban educational setting. This study implements a mixed-method using a hydrological analysis and a rational approach. To optimize this pond’s attribute to be a sustainable landscape element, this study employs a qualitative method by conducting an analysis founded on several sustainability indicators. Based on hydrological calculations, this study finds that the current condition has not met the standard for sustainability. The pond’s capacity to contain potential rainwater runoff and drainage water in the future is also estimated insufficient. Its function as a sustainable landscape element is also not ideal. So, the pond needs to be optimized by taking ecological, economic, socio-cultural, and architectural aspects into consideration, as well as making sure that supporting facilities such as signage, parking facilities, and necessary structures to support outdoor activities of Diponogore University’s academic community, are well provided. Keywords: retention pond, flood control, sustainable landscape, architecture, urban education area. Abstrak Kolam retensi merupakan salah satu bangunan pengendali banjir, yang sebagian besar dibuat untuk tujuan fungsional saja, tanpa memperhatikan alternatif objektif lain. Keberadaan kolam retensi di Universitas Diponegoro belum dimanfaatkan secara optimal. Kapasitas tampungnya menyusut karena mengalami pendangkalan serta kondisi di sekitarnya belum tertata. Agar optimal, dilakukan perhitungan dan analisis kondisi eksisting untuk direkomendasikan solusi optimalisasi dalam penataan lanskap yang berkelanjutan. Penelitian ini bertujuan mengetahui kelayakan kolam retensi sebagai pengendali banjir jangka panjang, dan bagaimana optimalisasi pemanfaatannya sebagai bagian dari elemen lanskap berkelanjutan pada kawasan pendidikan perkotaan. Metode yang digunakan adalah metode campuran, menggunakan analisis hidrologi dan pendekatan rasional. Untuk optimalisasi pemanfaatannya sebagai elemen lanskap digunakan metode kualitatif dengan analisis menggunakan indikator keberlanjutan. Dari perhitungan hidrologi, diketahui kondisi eksisting saat ini tidak cukup berkelanjutan. Daya dukungnya untuk potensi limpasan air hujan dan air drainase di masa depan diperkirakan tidak mencukupi. Fungsinya sebagai elemen lanskap juga belum optimal maka perlu dioptimalkan dengan memperhatikan aspek ekologis, ekonomi, sosial budaya dan arsitektural, serta memenuhi kelengkapan penunjang seperti signage, sarana parkir dan bangunan penunjang kegiatan outdoor bagi civitas akademika dari Universitas Diponogoro. Kata kunci: kolam retensi, pengendali banjir, lanskap berkelanjutan, arsitektur, kawasan pendidikan perkotaan.